Thoracolumbar traumatic nucleus pulposus sequestration combined with a slight flexion distraction fracture: A rare case report and literature review. Issue 25 (June 2018) - Yin, Ruofeng; Chang, Pengyu; Zhu, Qingsan; Cheng, Fei; Zhao, Baolin; Gu, Rui; Zhang, Bo-Yin
Abstract: Rationale: Traumatic nucleus pulposus sequestration (TNPS) usually occurs concurrently with severe destruction of bone. TNPS combined with a slight thoracolumbar flexion- distraction fracture, triggering a disastrous nerve injury, has rarely been reported. Due to the atypical radiologic manifestations, such a patient can easily be overlooked. Patient concerns: Hereby, we present a TNPS patient as well as a slight thoracolumbar flexion-distraction fracture and serious neurologic symptoms. Diagnoses: T12 spinous process fracture, L1 flexion distraction fracture, thoracolumbar traumatic nucleus pulposuse sequestration and lower limbs incomplete paralysis Interventions: To avoid further neurologic compromise, an urgent laminectomy and exploration of the spinal canal was performed. Outcomes: After decompression OR and 4 months rehabilitation, the patient's neurologic function improved remarkably. Lessons: A slight flexion-distraction fracture following injury is liable to eclipse the concurrence of TPNS. For this patient, a high-resolution MRI was needed to make a definitive diagnosis and guide surgery. Once TPNS has been diagnosed, sufficient decompression and discectomy surgery should be performed without delay.